An Analysis of Culture on the Reading Material Textbook in the Second Grade Junior High School - Fitriyah, Linda (Universitas Swadaya Gunung Jati, 2015)
In this research, the writer analyzed the culture in the English textbook entitled “When English Rings a Bell for VIII Grade Junior High School (SMP/ MTS)” written by Siti Wachidah et al published by Ministry of Education and Culture. The research was conducted to find out what are the cultures shown on the English textbook. The writer tried to analyze the four categories of culture that stated by Patrriick Morran in the reading material on the English textbook. She wrote a paper entitled “AN ANALYSIS OF CULTURE ON READING MATERIAL TEXTBOOK AT THE SECOND GRADE OF JUNIOR HIGH SCHOOL IN SMPN 10 CIREBON”. Textbook is the important thing in teaching and learning process (Tomlison, 1999:2). The textbook is for students that make 2013 curriculum in their school. Relying on this, the present study, how culture disseminated in he textbook. The data for this study are collected from an English textbook for second grade of junior high school. The data for the study are in the form of structural an the reading text passages. The structure is categorized and analyzed based on the framework culture four categorized proposed by Patrick Moran . The sample of this study analyzed trough the reading material on the first semester. This study use qualitative method. This study conducted at reading material on the first semester. Further, the reading material on the English textbook include used almost Indonesian culture. Further, the structural of textbook culture is Indonesian culture. The reading material also almost using Inodonesian culture. The textbook is easy to use because the textbook was familiar by students own culture, it presented names, action, places and characters of Indonesian culture.